Development, growth and challenges of Islamic capital markets: comparative insights from the Malaysian, Indonesian, United Arab Emirates and Brunei Markets / Syed Faiq Najeeb and Mirza Vejzagic. - Najeeb, Syed Faiq; Vejzagic, Mirza (Universiti Teknologi Mara Selangor, 2013)
Despite initiatives and discussions in many countries to introduce Islamic capital markets, the share of non-banking assets in the global Islamic finance industry remains small. Islamic banking continues to dominate the Islamic finance portfolio with a gigantic 80.9% contribution towards the total Islamic finance assets as at year end 2011. Based on such statistical reality, one may wonder, what are the current growth and development trends of Islamic Capital Markets (ICMs)? To this end, this paper assesses the development, growth and challenges of Islamic Capital Markets in Malaysia, Indonesia, United Arab Emirates, and Brunei and critically analyses the fundamental factors that contribute towards the liquidity, volume and trends of the Islamic Capital Markets in these countries. Using Malaysia as a benchmark, this paper provides a comparative analysis on the performance of the various sectors of Islamic capital markets such as equity markets, debt markets, fund management markets, liquidity markets, etc. amongst the four sample countries. In addition, the paper examines the local authorities‟ initiatives‟ and future plans for firmly establishing Islamic Capital Markets in their jurisdictions and further recommends potential policies that could be introduced to maximize economic gains and societal welfare from Islamic Capital Markets for the Muslim population in general. Overall, the findings from the paper are expected to attract significant interest from Islamic finance stakeholders, in particular to understand how local authorities and other players could possibly be instrumental in shaping the development of Islamic Capital Markets.